How do Mexicanas in the United States Perceive the police in Mexico? - Lim, Hyeyoung; Bontcheva Loyaga, Nadejda (Journal of Ethnic and Cultural Studies, 2024)
As an exploratory study, we examined policing in Mexico through the views of Mexicanas in the United States to understand better the relationships between the police and racial/ethnic minority communities in the United States. By understanding and knowing the perception and direct interaction with the police in their home countries, the U.S. police can better understand the attitudes of racial/ethnic minorities, particularly those foreign-born or of immigrant descent residents, toward the police. Besides, mutual understanding between the U.S. police and racial/ethnic minorities may assist in building better police-community relationships. For that reason, we conducted a semi-structured interviews with seventeen Mexicanas who resided in a Deep South state in the United States and explored their experiences and concerns with policing in Mexico. We found that government corruption and police politicization were the number one concern, and the widely accepted culture of bribing and taking a bribe was perceived as a common custom rule in Mexico. With consideration that such experiences are important to understand the relationships between the U.S. police and Mexicanas, policy implications and study limitations were further discussed in the current study.